ANALISIS KESALAHAN PENULISAN GORESAN KARAKTER MANDARIN MAHASISWA SEMESTER IV PRODI PENDIDIKAN BAHASA MANDARIN - Puspita, Mega Ayu; Santoso, Fansi Onita; Urip, Sri Rejeki (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2018)
Abstract___________________________________________________________________The Chinese character is China's biggest cultural heritagestill used today. Its an ideographical writing system which the pronunciation doesnt symbolize sound but represents the meanings. There are too many Chinese characters, so most students feel difficult to remember and in the process of writing these are often fail. This research uses descriptive qualitative method which aims to find out the errors in Chinese Department the fourth grade students to write strokes of Chinese character, analyzes the causes of the errors and give some advice to avoid the errors. Data collection technique was used by test and documentation method. Based on research result on the first part there are 10 types of mispronounced or wrongly written character and 4 types of incorrect character, on the second part there is a miscalculate strokes of Chinese character, and the third part there are 15 types of mispronounced or wrongly written character, 11 types of incorrect character and one type of error writing the strokes of Chinese character.The conclusion of the research shows that the error causes are: the same sound of Chinese character factor, the shape and structure character was similar to other character factor, Chineses radical factor and carelessness. According the factors causing above, there are some tips that can reduce and avoid the errors writing the strokes of Chinese character: students must understand the meaning of Chinese character, must to know well about the shape and structure of Chinese character, and must extend the exercise to write Chinese characters.Abstrak___________________________________________________________________Karakter Mandarin adalah warisan budaya terbesar Tiongkok yang masih digunakan hingga sekarang.Karakter Mandarin merupakan karakter yang memiliki lafal dan tidak melambangkan bunyi, tetapi menyatakan arti.Karena jumlahnya sangat banyak menyebabkan sebagian besar mahasiswa merasa kesulitan dan sering mengalami kesalahan penulisan goresan karakter Mandarin.Penelitian ini menggunakan pendekatan penelitian deskriptif kualitatif yang bertujuan mengetahui kesalahan penulisan goresan karakter Mandarin mahasiswa semester IV Prodi Pendidikan Bahasa Mandarin, menentukan faktor penyebab, dan merumuskan kiat yang dapat dilakukan untuk mengurangi kesalahan.Teknik pengumpulan data dilakukan dengan metode tes dan dokumentasi. Berdasarkan hasil analisis data soal bagian I terdapat 10 jenis kesalahan ??bi z dan 4 jenis kesalahan ??cu z, soal bagian II mengenai kesalahan menghitung jumlah goresan, dan soal bagian III terdapat 15 jenis kesalahan ??bi z, 11 jenis kesalahan ??cu z, dan 1 jenis kesalahan penulisan karakter Mandarin.Faktor penyebabnya karena pengaruh persamaan bunyi karakter Mandarin, bentuk karakter yang hampir mirip dengan karakter lainnya, radikal yang menyusun karakter, dan ketidakhati-hatian penulisan karakter.Dari faktor penyebab di atas, beberapa kiat agar dapat mengurangi terjadinya kesalahan penulisan yakni memahami makna karakter Mandarin, menguasai bentuk karakter Mandarin, dan memperbanyak latihan menulis.